Efficiently electron beam radiation-induced degradation and extraction of Angelica sinensis polysaccharides and its excellent biofunctional properties - Yunxia Hu; Xiao Liu; Haijun Wang; Zhijun Xin; Fanglei Chen; Fangli Hu; Bingkun Liu; Xihong Lu; Mengmeng Du; Xinshuo Ren; Zhuanzi Wang; Xuehu Li; et al. (Food Chemistry, 2026)

Synergistic effect of environmental protection tax reform and climate-adaptive city pilot on green technology innovation: Evidence from China - Ning Han; Peixian Liu; Dezhao Zhao; Fanglei Zhong; Yirun Xiang (Journal of Cleaner Production, 2026)

Designing metal-organic frameworks (MOFs) for advanced per- and polyfluoroalkyl substances (PFAS) management: Adsorption, detection, and degradation - Fanglei Liu; Jun Cheng; Yahui Guo; Weirong Yao; He Qian; Zhilong Yu; Tiancong Zhao; Yunfei Xie (Environmental Research, 2026)

Temporal Features of Gamma Activity of Hyper-direct Pathway Regulated by Dopamine Receptors in the Dyskinetic Rat - Pengfei Wang; Weina Dai; Hongmin Li; Weijie Li; Yang Wang; Yichang Liu; Le Wang; Fanglei Ye; Yuming Xu (Neuroscience Bulletin, 2026)

The government’s impact on the transformation of rural livelihoods in agropastoral regions: Aquantitative analysis of farmers’ perceptions of public services in Inner Mongolia, China - Fanglei Zhong; Yusong Liu; Yulian Ma; Yaolong Li; Miao He (Land Use Policy, 2025)

A new type of triploid fish derived from female Carassius auratus red var. × male Gobiocypris rarus - Fanglei Liu; Ziyi Huang; Xuanyi Zhang; Bei Li; Lujiao Duan; Jianming Yu; Qizhi Liu; Siyang Huang; Hongwen Liu; Qiuli Liang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

The formation and growth characteristics of an all-female hybrid crucian carp - Lujiao Duan; ChaoLiang Shen; Jingjing Lin; Xiaoxia Xiong; Huan Sun; Ziyi Huang; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Multi-omics reveals the molecular mechanisms of rapid growth in distant hybrid fish - Xuanyi Zhang; Fanglei Liu; Bei Li; Lujiao Duan; Jianming Yu; Ziyi Huang; SiYang Huang; Hongwen Liu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Subway opening enables urban green development: Evidence from difference-in-differences and double dual machine learning methods - Jiahao Yang; Peixian Liu; Fanglei Zhong; Ning Han (Journal of Environmental Management, 2025)

Efficiency and equity: Effect of urban agglomerations’ spatial structure on green development efficiency in China - Peixian Liu; Fanglei Zhong; Ning Han (Sustainable Cities and Society, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Porous organic polymers assisted aptamer signal amplification for enhanced photoeletrochemical detection of MUC1 - Jiayi Zhao; Luqing Chen; Fanglei Liu; Yan Liu; Jianing Ji; Guojian Chen; Guohai Yang; Xiaochen Dong; Lu-Lu Qu (Analytica Chimica Acta, 2024)

Implications of genetics and current protected areas for conservation of 5 endangered primates in China - Zhijin Liu; Guangjian Liu; Christian Roos; Ziming Wang; ZuoFu Xiang; Pingfen Zhu; Boshi Wang; Baoping Ren; Fanglei Shi; Huijuan Pan; Ming Li (Conservation Biology, 2015)
Most of China's 24–28 primate species are threatened with extinction. Habitat reduction and fragmentation are perhaps the greatest threats. We used published data from a conservation genetics study of 5 endangered primates in China (Rhinopithecus roxellana, R. bieti, R. brelichi, Trachypithecus francoisi, and T. leucocephalus); distribution data on these species; and the distribution, area, and location of protected areas to inform conservation strategies for these primates. All 5 species were separated into subpopulations with unique genetic components. Gene flow appeared to be strongly impeded by agricultural land, meadows used for grazing, highways, and humans dwellings. Most species declined severely or diverged concurrently as human population and crop land cover increased. Nature reserves were not evenly distributed across subpopulations with unique genetic backgrounds. Certain small subpopulations were severely fragmented and had higher extinction risk than others. Primate mobility is limited and their genetic structure is strong and susceptible to substantial loss of diversity due to local extinction. Thus, to maximize preservation of genetic diversity in all these primate species, our results suggest protection is required for all sub‐populations. Key priorities for their conservation include maintaining R. roxellana in Shennongjia national reserve, subpopulations S4 and S5 of R. bieti and of R. brelichi in Fanjingshan national reserve, subpopulation CGX of T. francoisi in central Guangxi Province, and all 3 T. leucocephalus sub‐populations in central Guangxi Province.